2020
DOI: 10.1016/j.jfma.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Talc exposure and risk of stomach cancer: Systematic review and meta-analysis of occupational cohort studies

Abstract: Talc powder is widely used in various industries, but the carcinogenic effects associated with talc are not well understood. The objective of this study was to estimate the risk of stomach cancer after occupational talc exposure. We conducted a meta-analysis was performed to calculate the meta-relative risk (mRR) of stomach cancer. We searched the MEDLINE, EMBASE, CNKI and Wanfang Data databases for publications prior to January 1, 2017 using talc, cancer, and mortality as the search terms. Only cohort studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A recent meta-analysis of 40 mortality cohort studies showed that asbestos is associated with a moderately increased risk of stomach cancer [31]. A recent meta-analysis of 13 observational studies showed that occupational talc exposure is associated with an increased risk of stomach cancer [32]. A significant relationship has been found between occupational crystalline silica exposure and gastric cancer [33].…”
Section: Risk Factorsmentioning
confidence: 99%
“…A recent meta-analysis of 40 mortality cohort studies showed that asbestos is associated with a moderately increased risk of stomach cancer [31]. A recent meta-analysis of 13 observational studies showed that occupational talc exposure is associated with an increased risk of stomach cancer [32]. A significant relationship has been found between occupational crystalline silica exposure and gastric cancer [33].…”
Section: Risk Factorsmentioning
confidence: 99%
“…The IARC has classified talc containing asbestos as “carcinogenic to humans” (group 1), inhaled talc without asbestos as "not classifiable as to carcinogenicity in humans" (group 3), and perineal talc application as possibly carcinogenic to humans (group 2B); however, ingested talc has not yet been evaluated. Our recent systemic review and meta-analysis showed that workers with occupational talc exposure had an increased standardized mortality ratios of 1.21 (95% CI: 1.03–1.42, p = 0.02) for stomach cancer [25]. In the subgroup analysis, however, our previous meta-analysis showed that workers exposed to talc without asbestos had a non-significantly increased SMR of 1.26 (95% CI: 0.97–1.63, p = 0.09), probably due to insufficient case number.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible carcinogenic effects of talc have been discussed in the literature. A systematic review (Chang et al, 2020) showed a positive association between occupational talc exposure and risk of stomach cancer; however, the association with talc with no detectable level of asbestos was not significant.…”
Section: Introductionmentioning
confidence: 99%